Perancangan Perangkat Lunak Perhitungan Biomekanik dengan Microsoft Visual Basic 6.0 - Maesa Alif Badra Fataya; Tiara Tiara; Surya Perdana (Universitas Indraprasta PGRI Jakarta, 2022)
Practicum Design of Industrial Engineering (DIE) I was one of the existing courses in Industrial Engineering University X. One of which is discussed in DIE I is Biomechanics. Biomechanics is one branch of ergonomics that discussed about body mechanics for doing a job. In practicum of DIE I included in biomechanics is the Recommended Weight Limit (RWL), Lifting Index (LI), Rapid Upper Limb Assessment (RULA), and Rapid Entire Body Assessment (REBA). During this time, the calculation method of RWL, LI, RULA, and REBA on practicum DIE I still manually which causes the calculation becomes longer further practicum be delayed. This research aims to make the Software of calculation biomechanics by using Microsoft Visual Basic 6.0. Software that is made just for calculating RWL, LI, RULA and REBA. Based on testing by respondents as many as 21 people found the average time of manual calculation and software calculation. In completing the calculation, manual calculation takes an average of 297.246 seconds, while calculation with Software takes an average of 32.584 seconds. So that with the completion of the software, the calculation of biomechanics can be quickly resolved.